Alzheimer's Pathogenesis and Its Link to the Mitochondrion. (20th April 2015) - Simoncini, C.; Orsucci, D.; Caldarazzo Ienco, E.; Siciliano, G.; Bonuccelli, U.; Mancuso, M.
Abstract : Alzheimer's disease (AD) is the most common form of dementia in the elderly. This neurodegenerative disorder is clinically characterized by impairment of cognitive functions and changes in behaviour and personality. The pathogenesis of AD is still unclear. Recent evidence supports some role of mitochondria dysfunction and oxidative stress in the development of the neurodegenerative process. In this review, we discuss the role of mitochondrial dysfunction in AD, focusing on the mechanisms that lead to mitochondrial impairment, oxidative stress, and neurodegeneration, a "vicious circle" that ends in dementia.